First Stranding Event of a Common Minke Whale (Balaenoptera acutorostrata Lacépède, 1804) Reported in the Gulf of Thailand - Rachawadee Chantra; Korakot Nganvongpanit; Patcharaporn Yaowasooth; Surasak Thongsukdee; Kongkiat Kitiwatthanawong; Cholawit Thongcharoenchaikit; Janine L. Brown; Promporn Piboon (Diversity, 2023)
On 5 September 2022, a dead baleen whale was found stranded at Laem Phak Bia, Phetchaburi, the Gulf of Thailand, Thailand but could not be identified because it was in an advanced stage of decomposition. It was first suspected to be Omura’s whale (Balaenoptera Omurai), as that is a common species in the Gulf of Thailand. However, the cranium morphology was different from B. omurai and more similar to the common minke whale (Balaenoptera acutorostrata) from the North Pacific Ocean, which has never been reported in Thai territorial waters. The mitochondrial DNA control region (D-loop) was then used to identify the species through the Basic Local Alignment Search Tool (BLAST) available at the National Center for Biotechnology Information (NCBI) GenBank, which resulted in a high percent identity, 96.49 to 98.84, with B. acutorostrata. A Bayesian phylogenetic tree was further used to confirm the species, which grouped with B. acutorostrata from the North Pacific Ocean. This study provides evidence of the first stranding event of B. acutorostrata in the Gulf of Thailand. It is new information that extends previous knowledge on the distribution of the common minke whale and raises the need for more active surveys of cetaceans in the South China Sea going forward.